Plasmon-Mediated Oxidase-like Activity on Ag@ZnS Heterostructured Hollow Nanowires for Rapid Visual Detection of Nitrite - Tian, Lin; Huang, Zijun; Lu, Xinhua; Wang, Tingjian; Cheng, Wenjing; Yang, Huimin; Huang, Tianzi; Li, Tongxiang; Li, Zhao (Inorganic chemistry, 2023)
Rational design of fast and sensitive determination of nitrite (NO ) from a complicated actual sample overtakes a crucial role in constructing a high-efficiency sensing platform. Herein, a visual NO sensing platform with outstanding selectivity, sensitivity, and stability based on a surface plasmon resonance (SPR)-enhanced oxidase-like activity has been proposed. Benefiting from the intrinsic photocatalytic activity and limited light penetration of ZnS, the oxidase-like activity based on ZnS decorated on Ag nanowires (Ag@ZnS) is determined. It is demonstrated that the electrons are generated efficiently on the surface of ZnS and then transferred into the hot electrons of Ag with the help of localized SPR excitation, thus greatly oxidating the colorless 3,3',5,5'-tetramethylbenzidine (TMB) to produce dark blue oxidized TMB (oxTMB). When nitrite is added into the reaction system, the oxTMB will selectively react with NO to generate diazotized oxTMB, leading to a visual color change from dark blue to light green and subsequently to dark yellow. Owing to the specific recognition between nitrite and oxTMB, the recovery of catalytic activity induced an enhanced colorimetric test with a wider linear range for NO determination, an ultralow detection limit of 0.1 μM, excellent selectivity, and practicability for application in real samples. This plasmon-enhanced oxidase-like activity not only provides a smart approach to realize a colorimetric assay with high sensitivity and simplicity but also modulates oxidase-like activities.